Identificación de Naegleria spp. y Acanthamoeba spp. en agua de fuentes de Ciudad Juárez, Chihuahua. - Hernández-Peña, Claudia Carolina (2020)
Free-living amoebae (AVL) are cosmopolitan protozoa capable of establishing serious parasitic infections of various kinds in humans and animals. The Acanthamoebaand Naegleriagenera have gained greater relevance since they have species that can behave as pathogenic and opportunistic parasites. Ciudad Juárez has 84 artificial fountains scattered throughout the city, of which there is no control of its water quality, and may be a focus of AVL proliferation of these genera. The objective of the study was to demonstrate the presence of Acanthamoebaspp. and Naegleriaspp. in water from artificial fountains. Three fountains were selected, that were sampled in the months of July and October 2019. Samples were processed by the centrifugation method and incubated at 37 °C for 5 days. The isolates were tested at 3, 20, 37 and 45 °C for temperature tolerance. Likewise, PCR was performed to identify the genus Acanthamoeba, and the positive strains were tested for salinity tolerance. Acanthamoebanegative strains were tested for flagellar transformation, and positive strains underwent PCR testing to identify the genus Naegleria. A total of 13 isolates were obtained, of which four were positive for Acanthamoebaspp. From the Acanthamoebaspp. identified, the M1P2-C strainhad the characteristic of growing up to 3.5% NaCl and 37 °C; while the M1P1-B, M2P1-B and M2P2-B strains did not grow in the presence of NaCl, but grew at 20 and 37 °C. Highlighting the M2P2-B strain that grew at 45 °C. Two isolates were identified as Naegleriaspp. The M2P2-A and M2P2-A strains, had the ability to grow at temperatures of 20 and 37 °C, where the first one also grew at 45 °C. In the present study, it was identified that amoebae of the Acanthamoebaand Naegleriagenera are present in the waters of artificial fountains in Ciudad Juárez.